2019
DOI: 10.1109/twc.2019.2908369
|View full text |Cite
|
Sign up to set email alerts
|

Analog MIMO Radio-Over-Copper Downlink With Space-Frequency to Space-Frequency Multiplexing for Multi-User 5G Indoor Deployments

Abstract: Radio access network (RAN) centralization is at the basis of current mobile networks, in which BaseBand Units (BBUs) and radio antenna units (RAUs) exchange over the FrontHaul (FH) digitized radio-frequency signals through protocols such as the common public radio interface. However, such architecture, as it stands, does not scale to the demands of multiple-antennas 5G systems, thus leading to drastic RAN paradigm changes. Differently from digital RAN architectures, we propose to overcome bandwidth/latency iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The Radio Dot System [8], sketched in Fig. 1.a, partly overcame this problem while the A-MIMO-RoC architecture [13], [14] was able to relay multiple RATs MIMO signals over multi-pair copper-cables by filling the entire cable bandwidth for each pair. The feasibility of the proposed A-MIMO-RoC system has been shown in [15] by leveraging the end-to-end testing capabilities of the TRIANGLE testbed [16].…”
Section: System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The Radio Dot System [8], sketched in Fig. 1.a, partly overcame this problem while the A-MIMO-RoC architecture [13], [14] was able to relay multiple RATs MIMO signals over multi-pair copper-cables by filling the entire cable bandwidth for each pair. The feasibility of the proposed A-MIMO-RoC system has been shown in [15] by leveraging the end-to-end testing capabilities of the TRIANGLE testbed [16].…”
Section: System Architecturementioning
confidence: 99%
“…Fig. 1.b shows the generic block diagram of the A-MIMO-RoC architecture [13], [15] where the BBU communicates with the terminals (UEs) as in Fig. 1.c, through the RRU by using remote antennas.…”
Section: System Architecturementioning
confidence: 99%
“…The problem of optimally designing SF2SF multiplexing is tackled for the A-MIMO-RoC downlink channel in single-and multi-UE settings in [17] and [18], respectively. In addition to all the issues due to the analog relaying of signals already mentioned for the uplink channel, the downlink SF2SF problem is complicated by the different power constraints that need to be jointly fulfilled both at the cable input and at the RRU antennas.…”
Section: A-mimo-roc: Numerical Analysis and Simulations Workmentioning
confidence: 99%
“…As a first step, [17] confirms the potential of SF2SF also for the single-UE downlink A-MIMO-RoC channel. Then, [18] shows that, in multi-UE settings, the SF2SF multiplexing optimization (performed at the RRU), jointly designed with digital precoding of the overall wired-plus-wireless channels (performed at the BBU) and UE ordering optimization, is able to cope with both multi-UE interference and analog FH impairments, thus providing substantial performance gains in terms of minimum rate guaranteed for all the UEs. Finally, [19] focuses on the precoder design problem proposing a nearly-optimal BBU precoding algorithm and RRU power amplification strategy for the multi-UE A-MIMO-RoC downlink channel.…”
Section: A-mimo-roc: Numerical Analysis and Simulations Workmentioning
confidence: 99%
“…However, it has been demonstrated that in order to achieve this performance figure, it is needed to define an opportune low-complexity/all-analog mapping of the RF signals at the RRU antennas onto a combination of twisted-pairs/frequency channels over the cable. This wiredwireless resource allocation strategy, denoted as Space-Frequency to Space-Frequency (SF2SF) multiplexing, has been shown to minimize interference among signals carried over different 4 twisted-pairs, hence enabling an efficient usage of the LAN cable bandwidth [11]- [14]. An alternative formulation/solution to the RoC wired-wireless resource scheduling problem has been recently presented for 4G systems [16], and then extended to 5G New Radio (NR) indoor architectures [17,18].…”
Section: Introductionmentioning
confidence: 99%